Between Informal Marriage and Legal Certainty: Determining Marital Status through Isbat Nikah at the South Jakarta Religious Court - Kartika Sari; Azmi Islami; Delpa Firdaus (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The phenomenon of unofficial marriages, or "nikah sirri," remains a complex issue in society, particularly regarding the legal status of the marriage and its impact on the rights of the wife and children. This study aims to analyze the factors contributing to unofficial marriages and the efforts to establish the legal status of such marriages in the Pancoran District, South Jakarta. The research uses a descriptive qualitative method with a case study approach. Data were collected through observations, interviews with advocates, religious leaders, staff from the Pancoran Marriage Office (KUA), and relevant documentation. The findings of the study indicate that (1) unofficial marriages have consequences, including the invalidity of the marriage status under national law and the absence of the husband's financial responsibility and inheritance rights for the wife and children; (2) the main factors contributing to nikah sirri include love, pregnancy outside of marriage, and family pressure; (3) efforts to validate the marriage status are carried out by applying for marriage registration (isbat nikah) at the Religious Court, which can legalize the marriage under state law. These findings offer new insights into the importance of validating marriage status for safeguarding family rights. [Fenomena perkawinan di bawah tangan atau nikah sirri masih menjadi isu kompleks di masyarakat, terutama terkait dengan status perkawinan yang tidak sah menurut hukum dan dampaknya terhadap hak-hak istri dan anak. Penelitian ini bertujuan untuk menganalisis faktor penyebab perkawinan di bawah tangan serta upaya penetapan status perkawinan tersebut di Kecamatan Pancoran, Jakarta Selatan. Metode yang digunakan adalah penelitian kualitatif deskriptif dengan pendekatan studi kasus. Data dikumpulkan melalui observasi, wawancara dengan advokat, penghulu, staf Kantor KUA Pancoran, serta dokumentasi terkait. Hasil penelitian menunjukkan bahwa (1) perkawinan di bawah tangan berdampak pada ketidakabsahan status perkawinan menurut hukum negara dan tidak adanya kewajiban nafkah serta hak waris dari suami kepada istri dan anak; (2) faktor penyebab utama nikah sirri meliputi faktor cinta, kehamilan di luar nikah, dan tekanan keluarga; (3) upaya penetapan status perkawinan dilakukan dengan mengajukan isbat nikah ke Pengadilan Agama, yang dapat mengesahkan perkawinan tersebut secara negara. Temuan ini memberikan pemahaman baru mengenai pentingnya penetapan status perkawinan yang sah bagi hak-hak keluarga.]